1980
DOI: 10.1104/pp.66.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Aging of Slices and Ethylene Treatment of Whole White Potato Tubers

Abstract: Cyanide-resistant 02 consumption can be stimulated by either treating whole white potato tubers (Norchip) with ethylene, in the presence of 100% 02, or aging slices obtained from untreated potato tubers. A comparison of alternative pathway activity elicited by either treatment was undertaken. The proportion of electrons flowing through the alternative path in the presence of intermediate concentrations of KCN and at various concentrations of salicylhydroxamic acid was identical in both cases. However, the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…We have previously demonstrated that ethylene-induction of CN-resistant respiration is not associated with increased glucose metabolism (9). In this regard, Table IV presents evidence for an increase in the affinity of mitochondrial membranes for lipoxygenase after the development of CN resistance.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…We have previously demonstrated that ethylene-induction of CN-resistant respiration is not associated with increased glucose metabolism (9). In this regard, Table IV presents evidence for an increase in the affinity of mitochondrial membranes for lipoxygenase after the development of CN resistance.…”
mentioning
confidence: 60%
“…02 consumption was not inhibited by 1 mm KCN, suggesting that a cyanide-resistant alternative pathway exists in these slices. KCN, in fact, slightly stimulated 02 consumption-a phenomenon of unknown origin (possibly due to the Pasteur effect in the presence of KCN) that was reported previously (9). SHAM and PG by themselves had little effect on 02 consumption.…”
mentioning
confidence: 79%
“…7/3/1. v/v) or by ageing of slices (Dizengremel and Lance 1976. Janes and Wiest 1980, Bonnerot et al 1985, Hiser and Mclntosh 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh tissue slices from tubers demonstrate respiration that is sensitive to cyanide while aged potato tuber slices exhibit cyanide-resistant respiration (3,11,29). However, the induction of alternative pathway respiration in aged slices could be mimicked in fresh slices if the tubers were treated with ethylene, ethanol, acetaldehyde, acetate, or cyanide for 24 h before slicing (1,13,14,24,27). These results have been interpreted to mean that the alternative pathway is present constitutively in tubers (20).…”
mentioning
confidence: 99%